Markov Processes and Economic Analysis: The Case of Migration - Kelley, Allen C.; Weiss, Leonard W. (Econometrica, 1969)
This paper compares the simple Markov process commonly used in migration studies with an economic model of migration where interregional wage differences are the equilibrating variables. Using the economic model, it appears unlikely that regional exit and entry rates will remain stable as the population is redistributed. As a result, both theory and empirical interstate migration evidence suggest that Markov migration projections will usually understate the population changes required before stochastic equilibrium is reached. IN RECENT YEARS the social sciences, and particularly economics, have experienced